2019 IEEE Global Communications Conference (GLOBECOM) 2019
DOI: 10.1109/globecom38437.2019.9014173
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation-Discarding Ordered-Statistic Decoding for Linear Block Codes

Abstract: In this paper, we propose an efficient reliability based segmentation-discarding decoding (SDD) algorithm for short block-length codes. A novel segmentation-discarding technique is proposed along with the stopping rule to significantly reduce the decoding complexity without a significant performance degradation compared to ordered statistics decoding (OSD). In the proposed decoder, the list of test error patterns (TEPs) is divided into several segments according to carefully selected boundaries and every segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This list is notably determined thanks to the computation of joint error probabilities for the most reliable bits, and allows to process only the most probable candidate codewords. In [16], the most reliable bits are partitioned into segments according to reliability thresholds depending of the received noisy codeword. Only some of the segments are then selected for flipping.…”
Section: Complexity Reductionmentioning
confidence: 99%
“…This list is notably determined thanks to the computation of joint error probabilities for the most reliable bits, and allows to process only the most probable candidate codewords. In [16], the most reliable bits are partitioned into segments according to reliability thresholds depending of the received noisy codeword. Only some of the segments are then selected for flipping.…”
Section: Complexity Reductionmentioning
confidence: 99%
“…These are mainly to terminate the decoding early, when a suitable candidate codeword is found, and to discard TEPs, which are less likely to generate promising codeword candidates. Other approaches introduced in [58], [59] can also be used to further reduce the complexity by searching through the TEPs in an optimal manner, which will result in finding the best codeword estimate faster. An efficient implementation in C has shown that the OSD decoding with sufficient and necessary conditions can run an order-5 OSD in a few µs per codeword [60].…”
Section: Osd Decoding Of Pr Codesmentioning
confidence: 99%
“…Recently, a threshold-based OSD decoder was able to reduce the number of tested codewords [10]. CA-OSD [10] and segmentation-discarding decoding [11] limit the number of valid codewords to improve performance. Probability-based OSD [12] calculates the promising probability and success probability to discard the candidate codewords.…”
Section: Introductionmentioning
confidence: 99%